ANALISA PERBANDINGAN SALES GROWTH PT.ANEKA TAMBANG TBK DENGAN PT. J RESOURCES ASIA PASIFIK TBK - M. Rizky Fernanda; Puji Muniarty (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2020)
In today's increasingly competitive industrialization era, every company must continuously improve its competitiveness. Increasing competition in both the domestic market and the international market requires companies to be able to maintain or gain a competitive advantage by paying full attention to the company's operational and financial activities. Companies are required to be able to improve performance and attract investors to get funds or increase business capital in order to survive and compete. Every company definitely wants a high level of profitability so that it can achieve the targeted profit level. one of the sources of profit from a company, especially a mining company, can be measured from its sales growth. Explicitly, high sales growth reflects the company's performance in a good and healthy position in financial reports by looking at the periodically increasing sales level. This study aims to analyze and determine whether there is a significant difference in sales growth between PT Aneka Tambang, Tbk and PT J. Resources Asia Pasifik, Tbk. This type of research is a comparative research type, which is comparing the presence of one or more variables in two different samples, or at different times. Data collection methods through documentation and literature study with samples, namely sales data of PT. Aneka Tambang TBK and PT. J Resource Asia Pacific TBK for 5 years from 2013 to 2018 using purposive sampling with the criteria (1) the available data component of the company's financial statements according to the needs of the researcher and (2) the data is up to date. The data analysis technique was using the independent sample test analysis, which was to determine whether there was a significant difference in the relation between the two independent groups with interphal data from the ratio. The results showed that the value of t count = 0.067 and the value of t table of 2.1009, with a sig of 0.948. meaning that the t value is smaller than the t table value and the sig value is greater than alpha so that in this case it reflects no difference and is not significant in sales growth of PT. Aneka Tambang Tbk and PT. J Resource Asia Pasifik Tbk.